2002
DOI: 10.1111/j.1748-0361.2002.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Services in Rural Areas: Is the Problem Geographic Access or Financial Access?

Abstract: Access to pharmacy services is an important rural health policy issue but limited research has been conducted on it. This article describes rural retail pharmacies in Minnesota, North Dakota, and South Dakota, including their organizational characteristics, staffing, services provided, and planned future changes; examines the availability of pharmacy services and pharmacy closures in rural areas of these three states; and briefly discusses policy issues that affect the delivery of pharmacy services in rural ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…Many rural hospitals rely on pharmacists who practice primarily in a community pharmacy setting. 3 As pharmacy service delivery has become increasingly complex, the knowledge and skills of pharmacists have become more specialized with respect to practice setting. It is unlikely that a pharmacist who is focused mostly on community pharmacy practice will be fully up-to-date with respect to the breadth of clinical and pharmacy systems management functions in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many rural hospitals rely on pharmacists who practice primarily in a community pharmacy setting. 3 As pharmacy service delivery has become increasingly complex, the knowledge and skills of pharmacists have become more specialized with respect to practice setting. It is unlikely that a pharmacist who is focused mostly on community pharmacy practice will be fully up-to-date with respect to the breadth of clinical and pharmacy systems management functions in an acute care setting.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition, a significant number of pharmacists in small rural hospitals practice primarily in community pharmacy settings, providing parttime pharmacist consultant services in hospitals and nursing homes in addition to their retail responsibilities. 3 Several studies have demonstrated that limited pharmacist hours adversely affect the contributions pharmacists can make to medication safety in rural hospitals. As a result of pharmacist vacancies, rural hospital pharmacists in Illinois reported a reduction in the amount of time available to provide clinical pharmacy services and an increase in pharmacy-related medication errors.…”
mentioning
confidence: 99%
“…A set of independent variables was chosen on the basis of regional socio-economic features, previous research (Casey et al, 2002;Perez and Decoupigny, 2009;Amstislavski et al, 2012;Norris et al, 2014;Qato et al, 2014) and data availability at the municipal level. This dataset included population (1000s of inhabitants)/population density (inhabitants per km 2 ), mean altitude (100 m units) above the mean sea level (msl), dummy variables of the status of rural according to the Eurostat classification (Istat, 2014), municipality (0=urban), coastal municipality (0=landlocked), proportion of >65-year-olds, <5-yearolds, immigrants, and a proxy of municipal income (mean declared personal income per taxpaper in 1000s of Euro).…”
Section: Study Variables and Data Sourcesmentioning
confidence: 99%
“…Research has shown that geographical access to pharmacies depends on several factors, such as socio-economic determinants (Casey et al, 2002;Amstislavski et al, 2012;Qato et al, 2014) including levels of deprivation (Ward et al, 2014;Todd et al, 2014), community segregation (Qato et al, 2014), landscape features (Perez and Decoupigny, 2009) and degree of urbanity vis-à-vis remoteness (Lin, 2004;Todd et al, 2014;Norris et al, 2014). Among these, urban-rural inequalities are of particular relevance in Italy, since rural areas account for more than 90% of the surface area and host about 57% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the relatively better pharmacy staffing pattern in urban areas compared to those of rural areas as rural pharmacies are likely to experience staff shortages. 43,44 Consequently, this may limit opportunities for interactions between pharmacists and the conduct of face-to-face, synchronous handoffs during shift changes. After-hours coverage for pharmacy services in rural areas are also likely to be limited and, as a result, patients may be forced to obtain services from other places such as hospitals or pharmacies located in a different community.…”
Section: Discussionmentioning
confidence: 99%